Mubadalah in the Transformation of Identity Politics in Indonesia: Challenges and Opportunities - Bustanul Arifin; Rudi Santoso; Mufid Arsyad (Journal of Islamic Mubadalah, 2024)
Identity politics in Indonesia is often influenced by social dynamics that are discriminatory towards gender. The concept of Mubadalah, meaning reciprocal or mutual, offers an inclusive approach to addressing gender injustice. This research examines the implementation of Mubadalah in transforming identity politics in Indonesia from 2009 to 2023. This study uses a qualitative approach with literature analysis, in-depth interviews with politicians, activists, and gender experts, as well as policy document analysis and election data. Findings indicate that Mubadalah-based education successfully changes traditional views on gender roles. Public policies adopting Mubadalah principles enhance women's representation in politics. Despite challenges from conservative groups, successes in several regions demonstrate the substantial potential of Mubadalah to achieve gender equality and justice in Indonesia.